2014
DOI: 10.1109/tdei.2014.004368
|View full text |Cite
|
Sign up to set email alerts
|

Artificial pollution flashover performance of porcelain long rod UHVDC insulators at high altitudes

Abstract: Porcelain long rod insulators are recommended for outdoor insulation of UHV/EHV dc transmission lines because of their excellent service experience obtained in Central Europe. However, very few studies have been conducted on dc pollution flashover performance or the UHVDC insulators at high altitudes. Artificial pollution tests on 300 kN and above porcelain long rod insulators were carried out with dc voltage in natural high altitude areas (about 2000 m), in which the solid layer method was used and the 50% fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The relationship between the flashover voltage along the surface and the number of arcs is shown in the Equations ( 8)- (12).…”
Section: Flashover Experiments Of Surface Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the flashover voltage along the surface and the number of arcs is shown in the Equations ( 8)- (12).…”
Section: Flashover Experiments Of Surface Pollutionmentioning
confidence: 99%
“…E. M. Savadkoohi et al found that there was a negative correlation between the flashover voltage of the insulators and the fan-shaped non-uniform pollution non-uniformity degree, which settles on them. The greater the unevenness, the more severe the flashover voltage attenuation will be [11,12]. Based on the above research, Wu et al studied the pollution agglomeration characteristics on the insulator surface under DC electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the rain flashover voltage gradient along the insulation height (Eh) can be gained by the following formula [17,18]:…”
Section: Procedures Of Flashover Testmentioning
confidence: 99%
“…With China's vigorous development of energy in the central and western regions, power transmission and transformation projects need to pass through high-altitude regions such as Southeast Tibet and West Mongolia. In Southeast Tibet, the potential sites for UHV converter stations are generally higher than 2000 m [1][2][3]. The increase in altitude will lead to a serious reduction in the strength of the external insulation of insulators, bushings, and other equipment in substations and converter stations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%